Mine Pressure Behavior Characteristics and Control Methods of a Reused Entry that Was Formed by Roof Cutting: A Case Study - Yajun Wang; Haosen Wang; Manchao He; Qi Wang; Yafei Qiao; Jun Yang (Shock and Vibration)
Noncoal pillar mining with automatic formation of a roadway is a new coal mining method that is tailored to improve the coal resource recovery rate and reduce the investment in roadway tunneling. Using this proposed method, a reuse entry is formed by roof cutting instead of tunneling. In this paper, the S1201-II working face of the Ningtiaota Coal Mine was used as a case study. The stress distribution of surrounding rock and the roof deformation characteristics of the reused entry during the mining process of the second working face were studied through FLAC3D numerical simulations combined with field measurements. The results indicate that the zone close to the reused entry led to higher stress in advance. If this stress is superimposed with the lateral pressure of the adjacent mined working face, it will be more difficult to maintain the reused entry. In the engineering case study described here, the reused entry created a stress increase zone and a severe deformation zone in the range of 0–80 m in front of the working face, and its range was approximately 37.5% larger than an ordinary entry. The stress peak in the stress increase zone increased by approximately 34.7% over that of an ordinary entry. The maximum amount of deformation within the severe deformation zone increased by 94.4% over that of an ordinary entry. To properly control the surrounding rock stress and deformation of the reused entry, a dynamic pressure bearing support in front of the working face with adaptability to the large roof deformation and high support strength is proposed here. Field application results showed that the final roof deformation with the dynamic pressure bearing support can be satisfactorily controlled within 110∼130 mm. These findings can provide a reference for researchers and field engineering technicians when engaging in the support work of reused entry.